Identifikasi Perkembangan Kognitif Anak Usia 5-6 Tahun di TK Adhyaksa 1 Jambi - Uswatul Hasni; Aura Diah Pasa; Lupia Subaidah; Wahyu Windari; Endang Siregar; Tantri Nur Indah (STKIP Subang, 2025)
The purpose of this study was to determine the cognitive development of hyperactive children aged 5 and 6 years at Adhyaksa 1 Kindergarten in Jambi, focusing on the memory domain based on Bloom's Taxonomy. These early childhood children are in the golden age, when appropriate stimulation is crucial, but children with hyperactivity disorder or attention deficit hyperactivity disorder (ADHD) often have difficulty concentrating and controlling behavior that has a negative impact. This study was conducted using a qualitative approach, a case study type. Data were collected through interviews and observations five times every month with parents as informants. Four measures of memory ability—naming, recognizing, imitating, and matching—were included in the research tool. Data collection techniques were carried out through observation and interviews. The results showed that the cognitive development of hyperactive children in the memory domain was more prominent in the ability to imitate and recognize, while the ability to name and match still requires continuous stimulation.